Monetary policy with reserves and CBDC: Optimality, equivalence, and politics - Dirk Niepelt (Swiss National Bank, Study Center Gerzensee, 2020)
We analyze policy in a two-tiered monetary system. Noncompetitive banks issue deposits while the central bank issues reserves and a retail CBDC. Monies differ with respect to operating costs and liquidity. We map the framework into a baseline business cycle model with "pseudo wedges" and derive optimal policy rules: Spreads satisfy modified Friedman rules and deposits must be taxed or subsidized. We generalize the Brunnermeier and Niepelt (2019) result on the macro irrelevance of CBDC but show that a deposit based payment system requires higher taxes. The model implies annual implicit subsidies to U.S. banks of up to 0.8 percent of GDP during the period 1999-2017.
Keywords: E42; E43; E51; E52; 330; Reserves; deposits; central bank digital currency; monetary policy; Friedman rule; equivalence; Ramsey policy; bank profits; money creation